The occurrence of taeniids of wolves in Liguria (northern Italy). Issue 2 (August 2015) - Gori, Francesca; Armua-Fernandez, Maria Teresa; Milanesi, Pietro; Serafini, Matteo; Magi, Marta; Deplazes, Peter; Macchioni, Fabio
Highlights Wolves are considered as definitive hosts for Echinococcus granulosus in Liguria, Italy. Scats were examinated and taeniid eggs isolated. Molecular species identification was performed through PCR analysis and sequencing. Taeniid species diagnosed document domestic, semi-domestic and wildlife cycles.